Podobe o cerkvi in religiji (na Slovenskom v 90-ih) - Toš, Niko 1934- (Ljubljana FDV-IDV [u.a.], 1999)
Engl. Zsfassungen
Includes bibliographical references
Summary in English
Keywords: Religiousness -- Public opinion; Public Opinion -- Slovenia; Catholic Church -- History -- 20th century -- Slovenia; Aufsatzsammlung